The vestibular implant: frequency-dependency of the electrically evoked vestibulo-ocular reflex in humans - van de Berg, Raymond; Guinand, Nils; Nguyen, T. A. Khoa; Ranieri, Maurizio; Cavuscens, Samuel; Guyot, Jean-Philippe; Stokroos, Robert; Kingma, Herman; Perez-Fornos, Angelica (Frontiers in Systems Neuroscience, 2015)
The Vestibulo-Ocular Reflex (VOR) shows frequency-dependent behavior. This study investigated whether the characteristics of the electrically evoked VOR (eVOR) elicited by a vestibular implant, showed the same frequency-dependency. Twelve vestibular electrodes implanted in 7 patients with bilateral vestibular hypofunction were tested. Stimuli consisted of amplitude-modulated electrical stimulation with a sinusoidal profile at frequencies of 0.5Hz, 1Hz, and 2Hz. The main characteristics of the eVOR were evaluated and compared to the “natural” VOR characteristics measured in a group of age-matched healthy volunteers who were subjected to horizontal whole body rotations with equivalent sinusoidal velocity profiles at the same frequencies. A strong and significant effect of frequency was observed in the total peak eye velocity of the eVOR. This effect was similar to that observed in the “natural” VOR. Other characteristics of the (e)VOR (angle, habituation-index, and asymmetry) showed no significant frequency-dependent effect. In conclusion, this study demonstrates that, at least at the specific (limited) frequency range tested, responses elicited by a vestibular implant closely mimic the frequency-dependency of the “normal” vestibular system.